Characterization of the dystrophin gene in Macrobrachium rosenbergii / Noor Anees Fathima - Noor Anees , Fathima (2016)
The dystrophin gene encodes one of the most crucial components of muscle fibers, the dystrophin protein. As the largest gene in humans, it plays an important role in maintaining cytoskeleton structure and normal muscle function. Its absence results in a mortal muscular disease characterized by muscle degeneration and dysfunction. Due to the complexity of dystrophin in humans, the majority of studies into the function of this gene have been conducted in simpler organisms. In this study, the Macrobrachium rosenbergii dystrophin was identified and computationally characterized through bioinformatics methods. Its protein domains were identified and compared to domains in homologous dystrophin sequences from other organisms. Differential expression of the dystrophin gene in response to White Spot Syndrome Virus (WSSV) was also studied. An immediate down regulation of dystrophin expression was observed upon WSSV infection, followed by a significant up regulation in the later stages of the infection. Due to the significance of intracellular calcium concentration in dystrophin deficiency studies, it was quantified in healthy M. rosenbergii muscle tissues as well as at different time points post WSSV infection. A two-fold increase in intracellular calcium concentration was seen followed by its stabilization 24 hours post infection, supporting existing theories of calcium-dystrophin relations in dystrophin deficient muscles. Similarly, Transmission Electron Microscope (TEM) comparison of healthy and infected M. rosenbergii muscle tissues morphology showed distinct deterioration of the muscle fibers and mitochondria. Several possible explanations for these observed changes were postulated and discussed in detail, including possible cleavage of dystrophin due to WSSV induced protease expression.